Pengaruh Financial Performance dan Kebijakan Dividen terhadap Harga Saham Selama Masa Pandemi pada Subsektor Transportasi di Bursa Efek Indonesia - Aprilianti, Kholilah; Isnurhadi, Isnurhadi; Malinda, Shelfi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of the Financial Performance projected by Return on Assets (ROA) and the Dividend Policy projected by the Dividend Payout Ratio (DPR) on Stock Prices. The research sample consisted of 12 transportation companies listed on the Indonesian Stock Exchange during the 2019-2021 pandemic. Secondary data in the form of financial statements were analyzed using multiple linear regression analysis. The results showed that Financial Performance had a significant positive effect on stock prices while dividend policy had no effect. Nonetheless, both variables affect stock prices together. This shows that the company's decision to distribute dividends or not, then it will not affect the stock prices directly. Keywords: Financial Performance, Return on Assets (ROA), Dividend Policy, Dividend Payout Ratio (DPR), Stock Price